1974
DOI: 10.1126/science.184.4136.572
|View full text |Cite
|
Sign up to set email alerts
|

Brain Capillary Blockage Produced by a Virulent Strain of Rodent Malaria

Abstract: A sudden enhancement in virulence of a mild Plasmodium berghei yoelii 17 x strain resulted in fulminating and fatal infections in CF1 and A/J mice. The virulent strain has maintained its characteristics after ten cyclical transmissions through Anopheles stephensi. The visible expression of virulence of the mutated strain is its ability to cross the blood-brain barrier and cause intravascular sequestration of injected erythrocytes and blockage of brain capillaries. We, therfore, believe that the virulent line o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
2

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 10 publications
2
28
2
Order By: Relevance
“…Further indirect evidence in support of the birthrate hypotheses comes from field data on severe disease: these are the positive link in P. falciparum between severe malaria and parasite multiplication potential measured in vitro (Chotivanich et al 2000), and the correlation between cytoadherence in vitro and the incidence of severe anaemia and therefore perhaps asexual multiplication rate. Laboratory studies that also support the birth-rate argument are the higher growth rate and higher sequestration in a highly virulent mutant clone of P. yoelii compared with avirulent clones (Yoeli & Hargreaves 1974;Yoeli et al 1975), and the lower acute phase growth rate and virulence in a line of P. falciparum that had lost the ability to sequester (Langreth & Peterson 1985). However, in another study of a non-sequestering line in P. chabaudi, the rate of acute phase growth was similar to that of sequestering lines (Gilks et al 1990).…”
Section: Molecular Mechanisms For Virulence In Relation To Parasite Fmentioning
confidence: 96%
See 2 more Smart Citations
“…Further indirect evidence in support of the birthrate hypotheses comes from field data on severe disease: these are the positive link in P. falciparum between severe malaria and parasite multiplication potential measured in vitro (Chotivanich et al 2000), and the correlation between cytoadherence in vitro and the incidence of severe anaemia and therefore perhaps asexual multiplication rate. Laboratory studies that also support the birth-rate argument are the higher growth rate and higher sequestration in a highly virulent mutant clone of P. yoelii compared with avirulent clones (Yoeli & Hargreaves 1974;Yoeli et al 1975), and the lower acute phase growth rate and virulence in a line of P. falciparum that had lost the ability to sequester (Langreth & Peterson 1985). However, in another study of a non-sequestering line in P. chabaudi, the rate of acute phase growth was similar to that of sequestering lines (Gilks et al 1990).…”
Section: Molecular Mechanisms For Virulence In Relation To Parasite Fmentioning
confidence: 96%
“…Lesions (Vuong et al 1999) and parasites (Mota et al 2000) have been found in the brain of P. chabaudi-infected mice, but most sequestration takes place in other vital organs such as the liver (Cox et al 1987;Mota et al 2000). Brain involvement similar to cerebral malaria does occur in related rodent species (P. berghei, Rest (1982) which also sequesters in other organs (Alger 1963), and in P. yoelii, Yoeli & Hargreaves 1974;Kaul et al 1994), but this appears to be only after adaptation to the novel host (mice) through serial passage. In addition to its similarities with P. falciparum, the P. chabaudi system is attractive as a model because of the availability of diverse parasite strains cryopreserved shortly after they were derived from the wild (Beale et al 1978), the availability of host genotypes with well-characterized genetics, the ability to measure virulence, multiplication rate, gametocyte production, transmission to mosquitoes, cytoadherence and antigenic variation in vivo, and the ability to manipulate immunity and other factors that moderate virulence.…”
Section: Plasmodium Chabaudi As a Model For Virulence Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of VSA-specific immunity to P. falciparum malaria have been frustrated by the lack of convenient and relevant animal models. Although rodent malaria parasites lack var gene orthologs, antigenic variation and IE sequestration occur with several Plasmodium species (1,19,23,41), and these species possess multigene families that appear to encode IE surface-expressed VSA (6,16). This fact notwithstanding, only limited information regarding the roles of the products of these gene families in pathogenesis and immunity is available (21,22).…”
mentioning
confidence: 99%
“…For this reason, we have focused our attention on the model of cerebral malaria induced by P. yoelii 17XL, initially described by Yoeli and Hargreaves. 10 This lethal strain of P. yoelii arose as a spontaneous mutation from the nonlethal strain P. yoelii 17XNL. We confirmed the plugging of capillaries with parasitized erythrocytes in the brains of mice infected with P. yoelii 17XL that occurred without significant inflammation.…”
mentioning
confidence: 99%